To solve the system of equations, we can use the method of substitution or elimination.
First, let's solve the first equation for y:
y = 12 + 9x
Then, substitute this expression for y into the second equation:
2x + 4(12 + 9x) = -28
2x + 48 + 36x = -28
38x + 48 = -28
38x = -76
x = -2
Now, substitute x = -2 back into the first equation to solve for y:
-9(-2) + y = 12
18 + y = 12
y = -6
Therefore, the solution to the system of equations is (-2, -6).
Solve the system of equations. –9x+y=12 2x+4y= −28 (1 point) (, )
1 answer